THE PROBLEM OF FORMATION OF LOCAL HISTORY PRINCIPLES AND LOCAL STUDIES IN THE WORKS OF SCIENTISTS - O.V. Bondarenko (Academy of Cognitive and Natural Sciences, 2022)
The article is devoted to the retrospective analysis of the development o f the local lore principle and study of local lore in the pedagogical literature.